Software Engineering Education in the DevOps Era: Experiences and Recommendations - Paez, Nicolás; Fontela, Carlos (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de Software, 2023)
DevOps has reached the mainstream, in part, because it proposed a way to solve the last mile of the software delivery process. It brought to the industry concrete solutions to some concerns that software engineering and academia have traditionally ignored. The popularity and success of DevOps got the attention of the academia and some universities have started to include DevOps related content in their programs. After doing our own experience, we found out that introducing DevOps is not as simple as adding a new course. In fact, it requires a major redesign of the Software Engineering curriculum. In this article we share some key ideas and recommendations to include DevOps in Software Engineering programs.